2019
DOI: 10.1111/bjet.12763
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive regulations in ICT‐supported flipped classroom interactions: An activity theory perspective

Abstract: In recent years, most studies on flipped classrooms or flipped learning have focused on learners' motivation, academic achievement and teachers' and students' perceptions of the flipped classroom. Little research has involved interactions in the flipped classroom. This study aims to show that in-class collaborative learning in the flipped classroom can not only be conceived as a collective activity consisting of discrete actions, but also as a systematic activity. From the activity-theoretical perspective, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 52 publications
1
31
0
4
Order By: Relevance
“…Flipped classroom is important as a culture transmission tool, because it uses videos during extracurricular time and supports enculturation of the individual by a more knowledgeable person and therefore ZPD (Steen-Utheim and Foldnes, 2018;Zheng et al, 2020). Also, in social aspect, the social structures, tools, and values are transmitted to students in extracurricular time.…”
Section: Conclusion Discussion and Suggestions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Flipped classroom is important as a culture transmission tool, because it uses videos during extracurricular time and supports enculturation of the individual by a more knowledgeable person and therefore ZPD (Steen-Utheim and Foldnes, 2018;Zheng et al, 2020). Also, in social aspect, the social structures, tools, and values are transmitted to students in extracurricular time.…”
Section: Conclusion Discussion and Suggestions For Future Researchmentioning
confidence: 99%
“…As a result of ZPD, the individual will work in the same group with a more knowledgeable peer and will improve themselves. Also, in a flipped classroom, the videos prepared by the teacher and more knowledgeable peers (Steen-Utheim and Foldnes, 2018;Zheng et al, 2020) will support the individual's learning.…”
Section: Conclusion Discussion and Suggestions For Future Researchmentioning
confidence: 99%
“…The issue is not limited to basic infrastructure equipment, but also to aspects related to its adoption in the classroom, the ability to clarify the educational opportunities it offers and to know the pedagogical paths that lead to its implementation [8]. For this reason, teachers must assume new methodological paradigms in which ICTs are included, promoting positive attitudes in students [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The study explored existing Contradictions in the teachers' practice, which enabled the researchers to see how PD might help teachers to resolve the Contradictions. Zheng, Kim, Lai and Hwang (2019) used Activity Theory at classroom level to explore flipped learning. In Zheng et al's study, the classroom was identified as a system and the use of Activity Theory enabled them to find Contradictions between all elements of the System and thus to make recommendations about how the implementation of flipped learning could be more effective.…”
Section: Rules Division Of Labourmentioning
confidence: 99%